A New Seamless Transfer Control Strategy of the Microgrid - Zhaoyun Zhang; Wei Chen; Zhe Zhang (The Scientific World Journal)
A microgrid may operate under two typical modes; the seamless transfer control of the microgrid is very important. The mode conversion controller is installed in microgrid and the control logic of master power is optimized for microgrid mode conversion. In the proposed scheme, master power is very important. The master-power is under the PQ control when microgrid is under grid-connected. And it is under V/F control when the microgrid is under islanding. The microgrid mode controller is used to solve the planned conversion. Three types of conversion are simulated in this paper. The simulation results show the correctness and validity of the mode control scheme. Finally, the implementation and application of the operation and control device are described.